The antenna near-field measurement error correction method based on Kriging interpolation - Li Zhihang; Zhang Wei (Dianzi Jishu Yingyong)
With the continuous advancement of antenna technology, the importance of near-field measurement techniques is also increasing. In near-field measurements, probe malfunctions or overly large sampling intervals can lead to significant errors in the extrapolated far-field pattern. To address this issue, a method for reducing near-field measurement errors based on Kriging interpolation is proposed. The study firstly simulates a rectangular aperture horn antenna using HFSS, then compares near-field data sampled at 1° intervals with data sampled at 6° intervals. Based on the 6° sampling data, 30% of the sampling points are randomly reduced, and missing data are filled using the Kriging interpolation method. The near-field to far-field transformation is then performed and compared with the simulated far-field results. The results indicate that, compared to the errors before interpolation, the error in the E-plane is reduced by 1.65 dB, and the error in the H-plane is reduced by 4.93 dB, while the number of sampling points is reduced by 30%. These findings demonstrate that the near-field data correction method based on Kriging interpolation can effectively reduce measurement errors, even maintaining high accuracy in the event of probe malfunctions.